1991
DOI: 10.1007/bf00403292
|View full text |Cite
|
Sign up to set email alerts
|

Height and glucose tolerance in adult subjects

Abstract: In a prospective study concerning the pathogenesis of impaired glucose tolerance and Type 2 (non-insulin-dependent) diabetes mellitus, 346 subjects with no clinical history of diabetes were given a standard 75 g oral glucose tolerance test. The expected positive associations between 120-min plasma glucose concentration and age and body mass index were observed in both sexes and between 120-min plasma glucose and waist/hip ratio in male subjects. An unexpected negative correlation was found between 120-min plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 9 publications
4
66
2
Order By: Relevance
“…Furthermore, the more insulin resistant GDM subjects had the greater decrease in adult height, resembling the Type II group. Our results thus agree with previous reports concerning Type II [1,2]. It could be speculated that the subset of GDM who will eventually develop permanent Type II are found among those whose stature is shorter than expected.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the more insulin resistant GDM subjects had the greater decrease in adult height, resembling the Type II group. Our results thus agree with previous reports concerning Type II [1,2]. It could be speculated that the subset of GDM who will eventually develop permanent Type II are found among those whose stature is shorter than expected.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that middle-aged patients with impaired glucose tolerance or Type II (non-insulin-dependent) diabetes mellitus are short compared with normal control subjects [1,2]. In middle-aged diabetic patients it is, however, difficult to exclude the effect of ageing and long standing metabolic effects on height.…”
mentioning
confidence: 99%
“…Several studies have shown that shorter stature is associated with higher 2hPG levels, [1,[18][19][20], and genetic or pre-and postnatal environmental factors have been suggested as explanatory mechanisms [21,22]. If the association between height and 2hPG levels is causally related to inherent metabolic abnormalities, we would expect HbA 1c levels to also be affected by height.…”
Section: Discussionmentioning
confidence: 98%
“…Height has been found to be inversely associated with diabetes and glucose intolerance in several studies [1,2,3,4,5] but the underlying mechanism for this association have not been understood. We have shown that leg length is the component of height that is inversely associated with diabetes whereas trunk length is not associated with diabetes.…”
Section: Discussionmentioning
confidence: 99%